ROMANCE JEANE MARIE IN BEAUTY AND THE BEAST - Maryuni Potabuga; Tini Mogea; Delly Sabudu (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
This research is mainly to find out the causes of conflict which are reflected in Brown's novel entitled Beauty and the Beast through characters named Belle and the ugly prince. In conducting his research, the writers use qualitative research because the data collected are in the form of words, not numbers. An objective approach is used in analyzing the data. The results of this study found that there are very valuable lessons and knowledge, especially those related to the love relationship between two characters who come from different backgrounds. It is also stated that Belle is finally able to fall in love with the Ugly Prince even though she knows that the prince is not like humans in general. Although there are the differences between them, however in the end the two of them can be together forever because of the power of Belle's love that can break the curse on the ugly prince.